Polymer Functionalization of Single-Walled Carbon Nanotubes using Living Polymerization Methods - Liu, Yuanqin (My University, 2004)
Single-w ailed carbon nanotubes (SWNTs) were oxidatively shortened and functionalized with ruthenium-based olefin metathesis catalysts. These catalyst-functionalized nanotubes were shown to be effective in the ring-opening metathesis polymerization of norbornene, resulting in rapid polymerization from the catalyst sites on the nanotube. It was found that high polymer molecular weights could be reached, and the molecular weight increased linearly with polymerization time. The resulting polynorbomene-functionalized nanotubes were found to exhibit solubility in organic solvents, while the starting materials and catalyst-functionalized nanotubes were completely insoluble. The polymerized materials were characterized by NMR, IR, DSC, AFM and TEM. Polystyrene and poly[(t-butyl acrylate)-b-styrene] with well-defined molecular weights and polydispersities were prepared by nitroxide-mediated free-radical polymerization. The homo- and block-copolymers were used to functionalize shortened single-walled carbon nanotubes (SWNTs) through a radical coupling reaction involving polymer-centered radicals generated at 125°C via loss of the stable free-radical nitroxide capping agent. The resulting polymer-SWNT composites were fully characterized and were found to be highly soluble in a variety of organic solvents. This solubility could also be altered through chemical modification of the appended polymers. The t-butyl groups of appended PtBA-b-PS could be removed to produce poly[(acrylic acid)-b-styrene]- functionalized carbon nanotubes. The resulting composite was found to form aggregates in a mixture of chloroform/methanol (v/v: 1/1), as determined by dynamic light scattering (DLS).
Keywords: functionalization; single-walled carbon nanotube; polymerization method